A new cycad stem from the Cretaceous in Argentina and its phylogenetic relationships with other Cycadales - Martínez, Leandro Carlos Alcides (2012)
The cycads are an ancient group of seed plants. Fossil stems assigned to the Cycadales are, however, rare and few descriptions of them exist. Here, a new genus of cycad stem, Wintucycas gen. nov., is described on the basis of specimens found in the Allen Formation (Upper Cretaceous) at the Salitral Ojo de Agua locality, Río Negro Province, Argentina. The most remarkable features of Wintucyas are: a columnar stem with persistent leaf bases, absence of cataphylls, a wide pith, medullary vascular bundles, mucilage canals and idioblasts; a polyxylic vascular cylinder; inverted xylem; and manoxylic wood. The new genus was included in a phylogenetic analysis and its relationships with fossil and extant genera of Cycadales were examined. In the resulting phylogenetic hypothesis, Wintucycas is circumscribed to subfamily Encephalartoideae, supporting the existence of a greater diversity of this group in South America during the Cretaceous.